Radiative heat exhaust in Alcator C-Mod I-mode plasmas. (8th March 2019) - Reinke, M.L.; Brunner, D.; Golfinopoulos, T.; Hubbard, A.E.; Hughes, J.W.; Kuang, A.Q.; LaBombard, B.; Marmar, E.; Mumgaard, R.; Terry, J.L.; Lore, J.; Canik, J.; et al.
Abstract: In order to more completely demonstrate the I-mode regime as a compelling fusion reactor operating scenario, the first dedicated attempts at I-mode radiative heat exhaust and detachment were carried out on Alcator C-Mod. Results conclusively show that within the parameter space explored, an I/L back-transition is triggered prior to meaningful reductions in parallel heat flux, , target temperature, and target pressure, at the outer divertor. The exact mechanism for the I/L trigger remains uncertain, but a multi-diagnostic investigation suggests the pedestal regulation physics is impacted promptly by small amounts of N2 seeded into the private flux region. The time delay between when N2 contacts the plasma and the I/L transition is triggered varied from 30–120 ms, approximately 0.7–, and the delay varied inversely with I-mode pedestal-top pressure, p   e, 95 . Power and nitrogen influx scans indicate that the I/L transitions are not linked to excessive bulk-plasma impurity radiation. It is also shown that in the subsequent L-mode following nitrogen seeding, and can be reduced by factors of 10. The I/L transition and L-mode exhaust results using N2 are compared to similar attempts using Ne where such and reductions in L-mode are limited to factors of 2–3. Implications for the I-mode regime are discussed, including needs for follow-up experiments on other facilities.